The evolution of Olympic judo: an events management and gender perspective - Allan, L.; Kiss, L. (The Arts and Sciences of Judo, 2024)
Judo, a martial art with deep historical roots, has transitioned from its origins in Japan to a globally re-cognised sport. The journey from its inaugural appearance at the Tokyo 1964 Olympics to its anticipated presence in Los Angeles 2028 reflects a dynamic evolution encompassing rule changes, more high-level competitions with prize money, evolving athleticism, technological innovations, improved understanding of safety and fairness, globalisation, and shifting cultural landscapes. This journey, far from linear, has seen periods of significant reform alongside moments of continuity, ultimately shaping the sport into the globally recognised spectacle we see today.This article explores the evolution of Olympic judo from the perspectives of the management of the competitions and gender equality, analysing key milestones and challenges that have shaped its modern form. The analysis focuses on two interconnected dimensions: the competition logistics and framework that underpin the management of judo as an Olympic sport, and the strides made toward gender parity within the sport. By investigating these aspects, we gain in-sights into how traditional sports adapt to modern values and expectations.